The Effect of Acemannan Hydrogel on Collagen Expression in Gingival Tissue of Diabetes Mellitus Animal Model - Chandra Susanto; Cindy Denhara Wijaya; Elzha Pratita Wijaya (HM Publisher, 2022)
Background: Diabetes mellitus is a comorbid disease that greatly interferes with the process of wound healing, including injuries to the gingival tissue. The Aloe vera plant, or Aloe vera, is one of Indonesia's natural wealth, which is often found and has been widely used by the community in overcoming various health problems, including to treat various wounds. This study aims to explore the potential of hydrogen acemannan to repair gingival tissue in rats with diabetes mellitus. Methods: An in vivo experimental study using 24 Wistar rats grouped into 4 groups (negative control, 25%, 50%, and 75% acemannan hydrogel). Collagen density was assessed histologically semiquantitatively. Data analysis was performed using SPSS using univariate, bivariate, and multivariate methods. Results: The administration of acemannan hydrogel showed an increase in the collagen density score along with an increase in the concentration of acemannan hydrogel. Administration of 25%, 50%, and 75% acemannan hydrogel showed significant differences in the collagen density score compared to the group that did not receive acemannan hydrogel treatment, p<0.05. Conclusion: Acemannan hydrogel application can increase collagen density in gingival tissue of diabetes mellitus animal model.